Physical activity interventions for the mental health of children: A systematic review. (2nd September 2022) - Hale, Gabrielle E.; Colquhoun, Luke; Lancastle, Deborah; Lewis, Nicky; Tyson, Philip J.
Abstract: Objective: This systematic review explored the effectiveness of using physical activity (PA) interventions to enhance psychological well‐being and reduce psychological ill‐being (e.g., anxiety and depression) in children aged six to 11 years old from the general population. Methods: Electronic databases were searched for studies published between January 2005 and June 2020: Web of Science, ProQuest Psychology Journals, PsycINFO, Pub Med, ASSIA, CINHAL PLUS, SPORTDiscus, EMBASE and Wiley Online Library. Search terms included 'physical activity intervention', 'psychological well‐being' and 'child*'. After removing duplicates, 11 390 studies were independently screened by two authors based on inclusion/exclusion criteria and assessed for risk of bias. Results: A total of 23 studies were narratively synthesized and categorized into four domains: Quality of Life (QOL), body image, self‐esteem and psychological ill‐being. Evidence was provided for the impact of PA interventions in improving QOL, body image and self‐esteem. Despite the positive effect on psychological well‐being, evidence for a reduction in the frequency and severity of symptoms associated with psychological ill‐being in children is less clear. Conclusions: Reviewed studies support the use of PA interventions in enhancing the psychological well‐being of children in school and community settings. More research is warranted to understand the impact of PA interventions on reducing psychological ill‐being in children from the general population.